Role of Ayurvedic Anticoagulant and Antioxidant Treatment in Covid-19 - Amrut.S. Salunke; Adarsh Ramkalap Sharma; Sonali Sunil Tadasarkar (International Journal of Ayurveda and Pharma Research, 2021)
Corona virus disease is caused by severe acute respiratory syndrome Corona virus 2[SARS-CoV-2] infections attacking multisystem of the human body at a time, of which respiratory system, immune system and circulatory system are most affected. The complications of the disease arise or it becomes more pronounced, after the cytokinine storm phase becomes established leading to hypercoagulative state affecting the circulatory and respiratory system. In Ayurveda, there is a holistic approach in treating the disease and the body as a whole. Drugs such as Haridra, Tulasi, Guduchi, Yashtimadhu, Twak, Triphala, Lavang, Maricha, Pippali etc and few Visha Dravyas like Langali, Dravanti etc can be used a single drug or a group of drugs with their phytochemical properties and active principles leading to delay and prevention of hyper coagulable states thereby preventing the cascade of complications caused by COVID, additionally having anti-inflammatory and immune-modulatory effect. Scientific research on these drugs may reveal a new approach for management and prevention of COVID related complications and can be a subject of future research interest.